Gambaran fungsi kognitif pada lansia di Desa Koka Kecamatan Tombulu - Manurung, Chandra H.; Karema, Winifred; Maja, Junita (e-CliniC, 2016)
Abstract: Impairment of cognitive function is the most cause of dependency in elderly. This occurs due to aging that causes anatomical changes such as waning of the brain and biochemical changes in the central nervous system. The purpose of this study was to determine the cognitive function in elderly people at Koka village, Tombulu district. This was a descriptive cross sectional study from primary mental health data. There were 53 respondents who were eligible to the inclusion criteria. This study showed the result of MMSE, 77.4% with a normal cognitive function, 20.8% with a probable cognitive disruption, and 1.8% with a definite cognitive disruption. This study showed from Mini Cog test, 64.2% with a normal cognitive function 28.3% with a probable cognitive disruption and 7.5% with a definite cognitive disruption. Conclusion: Based on the result, it can be concluded that most of the elderly people at Koka village, Tombulu district have a normal cognitive functionKeywords: cognitive function, elderly people, MMSE, mini cogÂ Abstrak: Dikalangan lansia, penurunan fungsi kognitif merupakan penyebab terbesar terjadinya ketergantungan terhadap orang lain untuk merawat diri sendiri. Hal ini disebabkan karena dengan semakin meningkatnya umur mengakibatkan perubahan-perubahan anatomi, seperti menyusutnya otak dan perubahan biokimiawi di Sistem Saraf Pusat (SSP). Tujuan dari penelitian ini adalah untuk mengetahui gambaran fungsi kognitif pada lansia di Desa Koka Kecamatan Tombulu. Bentuk peneltian ini adalah deskriptif, dengan menggunakan metode cross sectional dari data primer hasil pemeriksaan status mental. Sampel dalam penelitian ini berjumlah 53 orang yang sesuai kriteria inklusi dan bersedia menjadi responden. Hasil penelitian didapatkan bahwa dengan pemeriksaan MMSE 77.4% yang memiliki fungsi kognitif normal berjumlah, 20.8% dengan probable gangguan kognitif , dan 1.8% dengan definite gangguan kognitif, lalu hasil dengan pemeriksaan Mini Cog didapatkan 64.2% yang memiliki fungsi kognitif normal, 28.3% dengan probable gangguan kognitif dan 7.5% dengan definite gangguan kognitif. Simpulan: Dari hasil penelitian didapatkan bahwa sebagian besar lansia di Desa Koka Kecamatan Tombulu memiliki gambaran fungsi kognitif yang normal. Kata kunci: fungsi kognitif, lansia, MMSE, mini cog